Vehicle Volume Density Analysis in Nyomplong Road, Sukabumi City - Mochamad Ardi Maulana; Utamy Sukmayu Saputri; Ardin Rozadi (Nusa Putra University, 2021)
Jalan Nyomplong is a one-lane and two-lane road with a length of 400m. The cause of the congestion that occurs along Jalan Nyomp;long is the very high activity of residents and the condition of the road sections which are relatively small. In this study, data collection was obtained by conducting a survey for 1 day at 2 different location points around Jalan Nyomplong such as a survey of traffic volume, traffic speed, traffic density, and road segment capacity. In addition, supporting data is obtained from agencies and from social media. From the results of the study, it was found that the volume of vehicles recorded in the afternoon was the densest, the calculation of vehicle speed for on Jl. Nyomplong is 20 – 30 km/hour, density analysis for Jl. Nyomplong in the afternoon is the busiest at 59 vehicles/Km. Meanwhile, at this location, incoming vehicles are dominated from two directions Nyomplong – Jln Pabuaran or vice versa with a total in the morning (06.00-09:00) 2,032 vehicles/hour, during the day (12.00-15.00) 2,029 vehicles/hour and in the afternoon (16.00 -18.00) 3,040 vehicles/hour. In the analysis of road capacity calculated by the 1997 MKJI method, namely C = Co x FCw x FCsp x FCsf x FCcs (pcu/hour), the results found that the road capacity in the morning was 979 smp/hour, on during the day as many as 977 smp/hour, and in the afternoon as many as 1464 smp/hour.